A spiritual education course to enhance nursing students' spiritual competencies. (November 2020) - Chiang, Yi-Chien; Lee, Hsiang-Chun; Chu, Tsung-Lan; Han, Chin-Yen; Hsiao, Ya-Chu
Abstract: The study aimed to determine the impact of an elective spiritual education course for nursing students on spiritual competencies. A convenience sample of nursing students (N = 92) was recruited from a baccalaureate school of nursing between February and July 2016. The intervention group (n = 45) was comprised of students enrolled in the elective spiritual education course which integrated non-Christian Eastern cultural beliefs; the control group was comprised of students not enrolled in the elective (n = 47). A quasi-experimental design examined pretest, posttest, and follow-up data from students' self-administered questionnaires. The intervention effect of the course was analyzed using generalized estimation equation. The results indicated posttest scores among nursing students in the intervention group were significantly better than the comparison group for spiritual health. Practicum stress and professional commitment were significantly better at follow-up. Spiritual care attitudes, caring behavior, and religious belief were significantly improved from pretest to posttest, and at follow-up for the intervention group compared with the control group. In conclusion, a spiritual education course should be considered as a regular course in the nursing curriculum, which could improve students' spiritual competencies, individual spiritual growth, and the ability to care for patients.